sEMG analysis of muscle fatigue during prolonged driving - Eltayeb, Muhammad Alfatih; Azmi, Nur Liyana; Md Nor, Khairul Affendy; Toha, Siti Fauziah; Hassan Abdalla Hashim, Aisha; Nordin, Nor Hidayati Diyana (Persatuan Saintis Muslim Malaysia (PERINTIS), 2025)
Back pain is one of the most common health problems faced by people with long daily driving activity. One of the causes is spinal muscle fatigue. Surface Electromyography (sEMG) is the measurement of the electrical activity of muscles by using surface electrodes, providing insights into muscle performance and fatigue levels. In this study, sEMG measurements are used to evaluate low back muscle (Erector Spinae, Longissimus) fatigue while driving at 90-, 100-, and 110-degrees backrest inclination angle. The EMG signal is filtered and mean and median frequencies (MNF and MDF respectively) are calculated through a sliding window of one second with half a second step size. The results show varying signs of fatigue by the two indicators: MDF at 90 and 110 degrees while MNF indicated fatigue at 100 degrees inclination angle